2022
DOI: 10.1155/2022/1509000
|View full text |Cite|
|
Sign up to set email alerts
|

Network Blockchain Security Sharing Model Based on Fuzzy Logic

Abstract: In light of the continuous development of Internet technology, many problems involving network security based on the blockchain have also been observed gradually. In this paper, the existence forms of network security hazards based on the blockchain are explored to establish a network blockchain security sharing model based on fuzzy logic. In security sharing, network blockchains are often maintained by many parties. This poses new potential threats and challenges to privacy protection in these multiparty netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Cipher design: Fuzzy logic's complex substitution and permutation functions inhibit differential and linear cryptanalysis, making cryptography safer and quicker. [25,26]. 2.…”
Section: B Fuzzy Logic Role In Cryptographymentioning
confidence: 99%
“…Cipher design: Fuzzy logic's complex substitution and permutation functions inhibit differential and linear cryptanalysis, making cryptography safer and quicker. [25,26]. 2.…”
Section: B Fuzzy Logic Role In Cryptographymentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%